Barriers to childhood tuberculosis case detection and management in Cambodia: the perspectives of healthcare providers and caregivers - Yom An; Alvin Kuo Jing Teo; Chan Yuda Huot; Sivanna Tieng; Kim Eam Khun; Sok Heng Pheng; Chhenglay Leng; Serongkea Deng; Ngak Song; Daisuke Nonaka; Siyan Yi (BMC Infectious Diseases, 2023)
Abstract Background Diagnosis and treatment of tuberculosis (TB) in children remain challenging, particularly in resource-limited settings. Healthcare providers and caregivers are critical in improving childhood TB screening and treatment. This study aimed to determine the barriers to childhood TB detection and management from the perspectives of healthcare providers and caregivers in Cambodia. Method We conducted this qualitative study between November and December 2020. Data collection included in-depth interviews with 16 healthcare providers purposively selected from four operational districts and 28 caregivers of children with TB and children in close contact with bacteriologically confirmed pulmonary TB residing in the catchment areas of the selected health centers. Data were analyzed using thematic analyses. Results Mean ages of healthcare providers and caregivers were 40.2 years (standard deviation [SD] 11.9) and 47.9 years (SD 14.6), respectively. Male was predominant among healthcare providers (93.8%). Three-fourths of caregivers were female, and 28.6% were grandparents. Inadequate TB staff, limited knowledge on childhood TB, poor collaboration among healthcare providers in different units on TB screening and management, limited quality of TB diagnostic tools, and interruption of supplies of childhood TB medicines due to maldistribution from higher levels to health facilities were the key barriers to childhood TB case detection and management. Caregivers reported transportation costs to and from health facilities, out-of-pocket expenditure, time-consuming, and no clear explanation from healthcare providers as barriers to childhood TB care-seeking. Aging caregivers with poor physical conditions, lack of collaboration from caregivers, ignorance of healthcare provider's advice, and parent movement were also identified as barriers to childhood TB case detection and management. Conclusions The national TB program should further invest in staff development for TB, scale-up appropriate TB diagnostic tools and ensure its functionalities, such as rapid molecular diagnostic systems and X-ray machines, and strengthen childhood TB drug management at all levels. These may include drug forecasting, precise drug distribution and monitoring mechanism, and increasing community awareness about TB to increase community engagement.